The styles of coping with stress in team and individual athletes based on gender and championship level - Tasaddoghi, Z. (Annals of Applied Sport Science, 2013)
The purpose of this research is Prioritization coping with stress styles in individual and team athletes with an emphasis on gender and the level of championship. The population is 1092 athletes participate in team sports (volleyball, basketball, footsall and handball) and individual sports (ping pong, badminton, track & field, physical fitness, taekwondo and karate) with at least one year championship background. The sampling was selected by considering the lost subject 380 person one by one. For data collection in this research, has been used a 32 items questionnaire of Coping Scale Korea Atletes (CSKA) related to coping with stress styles. Questionnaires were distributed in pilot studies and their reliability was estimated a = 0.81. Data has been analyzed by using Mann Whitney U and in the level of P = 0.05. The results of this research indicated that problem focused coping and emotional coping style were higher priority than avoidance coping style and intuitive coping style. Male use the avoidance coping more than female and individual athletes apply problem focused coping more than group athletes. There is significant difference among athletes with different levels of sport achievement only in avoidance coping. The athletes according to background, genus, and kind of sport, education and levels of sport achievement use different coping style which this subject should be considered by coaches.